Pengaruh Pengungkapan Intellectual Capital, Profitabilitas, Dan Islamic Social Reporting Terhadap Nilai Perusahaan - Puspitasari, Ardea Nur; Warno, Warno; Wijayanti, Riska (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
The purpose of this study is to determine the effect of intellectual capital, profitability, and Islamic social reporting on Firm value. This type of research uses a quantitative method with multiple linear regression data analysis techniques. The data used in this study are secondary data. The population of this study is Islamic Commercial Banks registered with the Financial Services Authority in the period 2020-2023. The sample used is the purposive sampling method, totaling 8 samples. The results of this study indicate that first, Intellectual Capital has no effect on company value. Second, Profitability has a positive and significant effect on company value. Third, Islamic social reporting has no effect on Firm value.Keywords: intellectual capital, profitability, islamic social reporting, firm value